Mental health and active methodologies in medical graduation (Research, Society and Development, 2022)
Introduction: The active methodologies, for having a learning process that covers several pedagogical models, require full dedication of the students, fact that can trigger or aggravate psychic disorders. Objectives: To demonstrate the influence of active methodologies on the development of emotional changes in medical students and to analyze the temporal relationship of psychosocial degradation with the increase in the level of demand experienced during graduation. Methods: A cross-sectional study with a qualitative, experimental and participatory approach was used. The analyzed population consisted of 135 medical students from a private institution, 40 from the first, 51 from the fourth and 44 from the eighth semester. The WHOQOL-BREF questionnaire, based on the book “Mental Health Assessment Instruments” was used for data collection, which were treated using descriptive statistics, expressed as absolute and relative frequencies. Results: Results were obtained that describe sleep alterations in 125 individuals, emotional alterations such as anxiety, nervousness and discouragement with 108, 86 and 48 responses, respectively, in addition to the presence of a feeling that it is not worth living at least once in life. week identified in 56 individuals. Thus, when compared to the results obtained from 91 individuals reporting emotional changes being related to the application of the methodologies. Conclusion: The data presented demonstrated the association of active methodologies with the development of depressive disorders, evidencing a predominantly negative causality, making an integrative psychosocial intervention necessary.